Becoming a Psychotherapist: Learning Practices and Identity Construction Across Communities of Practice - Alby, Francesca; Zucchermaglio, Cristina; Fatigante, Marilena (Frontiers in Psychology, 2022)
Within a perspective that views groups as communities of practice and sites of construction of knowledge, learning and identity, this article aims to explore the contribution that participation in different groups over the course of one’s life provides to the development of professional practices of psychotherapist trainees enrolled in an Italian graduate school in group psychotherapy. Through qualitative analyses of 10 semi-structured interviews, our study empirically shows that, by participating in groups, the trainees not only learn the practices of that group but develop a sort of meta-learning which takes place across groups. The results highlight that: 1) transversality, duration and informality are found to be the group properties with the highest formative value; 2) learning practices across different groups have common characteristics: are organized around complex topics of group life (e.g. how to manage conflicts, how to join and leave groups, etc.), begin in early group experiences, are in continuous evolution, are associated with a critical event and a negative affect. At the same time it seems that these critical events are exactly what trigger and sustain learning practices. Data from interviews also show how professional identities are constructed as the outcome of learning in different communities of practice. The study outlines how the experience made in different groups is elaborated in and through meaningful self-narratives, highlighting them as a fundamentally collective, culturally-shaped sense-making process. Overall, these results contribute to a better understanding of learning processes as situated and jointly constructed through multiple group participations over time. Furthermore, they contribute to highlighting the role of self-narratives as a primary way through which trainees shape their identity as self-reflexive professionals competent in reading group dynamics. Directions for future research and suggestions for psychotherapist training paths are outlined in the conclusions.